OWASP Top 10 -listan riittävyys kyberturvallisessa verkkosovelluskehityksessä - Jormakka, Tomi (2023)
This bachelor's thesis delves into the ten most common risks in web application development, based on the OWASP (Open Web Application Security Project) Top 10 list available on their website. The thesis aims to address the question of whether the OWASP Top 10 list is sufficient when discussing cybersecurity in web application development. OWASP is one of the most well-known international communities in the field of cybersecurity, with a mission to enhance safer web application development practices. The thesis employs a descriptive literature review methodology. The sources for the thesis have been gathered from the following databases: the Association for Computing Machinery and Google Scholar. The findings indicate that the OWASP Top 10 list serves as a solid foundation for cybersecurity in web application development. However, it is acknowledged that the Top 10 list does not cover all aspects of cybersecurity in web application development, as the field continues to evolve along with its technologies and trends. Therefore, adopting a model of continuous learning is recommended for those engaged in web application development.